Impact of electronic trading platforms on the brokered interdealer market for Government of Canada benchmark bonds - Natasha Khan (Bank of Canada, 2007)
This study examines the impact of increased transparency, brought about by the introduction of three electronic trading systems, on the brokered interdealer market for Government of Canada benchmark securities. Using the CanPX dataset for the 2-, 5-, 10-, and 30-year benchmarks, the paper finds some evidence of decreased bid-ask spreads for the 30-year benchmark in the months following the introduction of the electronic platforms. Bid-ask spreads are not significantly different in the pre- and post-transparency periods for the 2-, 5- or 10-year benchmarks. The price-impact coefficient, calculated using dollar value as a measure of order flow, also decreased in the post-event period for the 30-year benchmark but is not statistically different for any of the other benchmarks. Overall, there is little evidence that liquidity improved or was lowered by the introduction of the electronic systems.
Keywords: G10; G14; 330; Financial markets; Market structure and pricing; Finanzmarkt; Rentenmarkt; Öffentliche Anleihe; Elektronisches Handelssystem; Kanada